Effect of contact and no-contact small-sided games on elite handball players - Dello Iacono, Antonio; Martone, Domenico; Zagatto, Alessandro Moura [UNESP]; Meckel, Yoav; Sindiani, Mahmood; Milic, Mirjana; Padulo, Johnny (Taylor & Francis, 2018)
This study aimed to investigate the effect of contact (C-SSG) and no-contact (NC-SSG) handball small-sided games (SSGs) on motion patterns and physiological responses of elite handball players. Twelve male handball players performed 10 C-SSG and 10 NC-SSG while being monitored through the heart rate (HR) and rate of perceived exertion (RPE) as physiological responses and time-motion activities profile using video-match analysis. Both game conditions resulted in similar HR responses (P > 0.05), but the NC-SSG led to a higher RPE scores. The time-motion activity analysis featured NC-SSG with a greater amount of walking (855.6 ± 25.1 vs. 690.6 ± 35.2 m) and backward movements (187.5 ± 12.3 vs. 142.5 ± 8.7 m) combined with fast running (232.3 ± 8.5 vs. 159.7 ± 5.7 m) and sprinting (79.5 ± 4.7 vs. 39.7 ± 3.7 m) activities (P < 0.001). Conversely, C-SSG had a higher percentage of jogging and sideway movements associated with greater frequency of jumping (0.87 ± 0.09 vs. 0.31 ± 0.06 nr) and physical contact (1.82 ± 0.55 vs. 0.25 ± 0.03 nr) events (P < 0.001). No between-regimen differences were found for the number of throws (P = 0.745). In addition, the RPE was significantly correlated with fast running relative distances (r = 0.909, P < 0.001) and sprinting relative distances (r = 0.939, P < 0.001). In conclusion, this investigation showed that both C-SSG and NC-SSG in team handball can effectively represent specifically oriented exercises, according to the sport-task and the performance demands.
Keywords: heart rate; metabolic demand; Notational analysis; rating perception effort; team sport